No Global War? A Role for Democratic Global Federalism - Myron J. Frankman (Journal of World-Systems Research, 2015)
In fact, the issue is not whether we shall be governed globally, but rather by whom and on what basis. The international realm is not one of anarchy as the realists would have us believe, but rather one of order: of rules, procedures and accepted norms of behavior associated in part with what are termed "international regimes" (Krasner 1983), each dedicated in principle to a separate functional domain. Global governance is not something that is to be created, but rather something to be altered in the public interest. The governance of the globe is currently configured by a shifting set of ill-coordinated actors: among them the one remaining super-power and, to a lesser extent, other strong states, as well as powerful individuals and a number of large transnational corporations and financial institutions. Whereas Le Monde Diplomatique (1995) speaks oflcs nouveaux maitres du monde, Robert Cox has summed up our current system of global governance with the phrase nebuleuse: "There is, in effect, no explicit political or authority structure for the global economy. There is, nevertheless, something there that remains to be deciphered, something that could be described by the French word nebulcuse or by the notion of 'governance without government."'